The effect of auditor's competence, experience, professional ethics, and auditor's professional skepticism on the auditor's ability in detecting fraud - Salman Jumaili; Sri Rahayu; Rahayu Rahayu (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The Internal Auditor in Higher Education is the Internal Supervision Unit which is a Lecturer with Additional Tasks appointed by the Higher Education Leader whose task is to assist the leader in supervising, evaluating, and reviewing non-academic activities. This study analyzes the influence of competence, experience of auditors, professional ethics, and professional skepticism of auditors on the ability of auditors to detect fraud (Survey of SPI Members of State Universities in Indonesia). This study used a questionnaire survey method with the number of respondents 47 people. The data is processed using smart PLS 3.0. The results of the study indicate that in the SPI PTN members, only Competence affects the Auditor's Ability to Detect Fraud, while the other variables are Auditor Experience, Professional Ethics, and Auditor Professional Skepticism have no effect.